Drug Use as a Risk Factor of Moral Disengagement: A Study on Drug Traffickers and Offenders against Other Persons - D'Urso, Giulio (Psychiatr Psychol Law, 2018)
This study investigates the moral-disengagement strategies and influence of drug use in adolescence on 49 offenders in Italian jails, 30 of which are drug traffickers and 19 of which are offenders against other persons. A semi-structured interview was conducted to collect data on family, social and medical histories and the manner in which the deviant act was carried out, and the Moral Disengagement Scale was used to identify specific moral disengagement mechanisms. The results show that the traffickers reported higher levels of general moral disengagement, dehumanization of victims, and advantageous comparison with respect to offenders against other persons. However, the offenders who used drugs in adolescence reported higher levels of advantageous comparison with respect to offenders who did not use drugs. Studying self-regulatory mechanisms is important for enriching the literature about risk factors connected with moral disengagement and deviant behaviour committed by offenders in order to implement the promotion of effective and targeted treatment and educational strategies.